Retrospective analysis of T-lymphocyte subsets and cytokines in malignant obstructive jaundice before and after external and internal biliary drainage - An, Jianli (J Int Med Res, 2021)
OBJECTIVE: To study changes in T lymphocyte subsets, cytokines, and liver enzymes in patients with malignant obstructive jaundice (MOJ) before and after external biliary drainage (percutaneous transhepatic cholangiography drainage, PTCD) and internal biliary drainage (percutaneous transhepatic insertion of biliary stents, PTIBS). METHODS: MOJ patients undergoing PTCD (n = 44) and PTIBS (n = 38) at our hospital were enrolled in the study from January 2017 until December 2019. Peripheral blood total bilirubin (TBIL), direct bilirubin (DBIL), aspartate aminotransferase (AST), alanine aminotransferase (ALT), CD3(+)%, CD4(+)%, CD4(+)/CD8(+) ratio, interleukin (IL)-2, IL-6, and tumor necrosis factor (TNF)-α were measured before and 1 week after biliary drainage. RESULTS: There was no significant difference in any parameter between the two groups before biliary drainage. TBIL, DBIL, AST and ALT following PTCD were significantly lower than before PTCD. By contrast, CD3(+)%, CD4(+)%, CD4(+)/CD8(+) ratio, IL-2, IL-6 and TNF-α showed no significant difference before and 1 week after PTCD. TBIL, DBIL, AST, ALT, IL-6 and TNF-α were significantly lower following PTIBS than before PTIBS. CD3(+)%, CD4(+)%, CD4(+)/CD8(+) ratio and IL-2 were significantly higher following PTIBS than before PTIBS. CONCLUSION: Both PTCD and PTIBS were effective for treatment of MOJ, but PTIBS was more beneficial for recovery of immune function.